PERNIKAHAN SESAMA JENIS DI SEJUMLAH NEGARA DAN PANDANGAN HAK ASASI MANUSIA - NIM. A1011191179, RASYID RIDA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Marriage is one of the human rights that must be protected and provided by the government to its people, this has also been regulated in Article 16 of the Duham, but today we are faced with an incident where there is a group, namely LGBTQ, who wants equality in the legality of same-sex marriage. based on